INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN: PERSPEKTIF DAN TANTANGAN GURU DI SMPN 21 MATARAM - Haerani; Rispawati; Basariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore teachers’ perspectives and challenges in integratinglocal wisdom into Civics Education (PPKn) learning at SMPN 21 Mataram. Using aqualitative descriptive method, the research involved four informants: a Civicsteacher, the principal, the vice principal of curriculum and students. Data werecollected through interviews, observation and documentation and analyzed usingMiles, Huberman and Saldana’s interactive model. The findings indicate thatteachers perceive local wisdom as essential for contextualizing PPKn learning andstrengthening students’ character values. Local traditions such as Bau Nyale andPeresean were integrated as learning resources to internalize Pancasila values.However, challenges include limited teaching materials, time constraints and thedifficulty of aligning all PPKn topics with local cultural contexts. The studyconcludes that integrating local wisdom enriches Civics Education but requiresadequate support, innovative strategies and collaborative efforts.